2007
DOI: 10.3182/20071107-3-fr-3907.00052
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Qos Support in Wireless Sensor Networks: A Survey

Abstract: Real-time wireless sensor networks are becoming more and more important by the requirement of message delivery timeliness in emerging new applications. Supporting real-time QoS in sensor networks faces severe challenges due to the wireless nature, limited resource, low node reliability, distributed architecture and dynamic network topology. There are tradeoffs between different application requirements including energy efficiency and delay performance. This paper studies the state of the art of current real-ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 24 publications
(19 reference statements)
0
68
0
1
Order By: Relevance
“…In papers [6], [7] authors pointed out various challenges and open research issues like; RT and energy aware, RT and multiple QoS (reliability, band width efficient…etc) requirements, RT capability for multiple sources and multiple sinks, cross layer design to meet the HRT requirements and RT support for the special application scenarios. From the above literature, it is observed that the issues like…”
Section: Challenges and Open Research Issues In Real Time Routing In Wsnmentioning
confidence: 99%
See 1 more Smart Citation
“…In papers [6], [7] authors pointed out various challenges and open research issues like; RT and energy aware, RT and multiple QoS (reliability, band width efficient…etc) requirements, RT capability for multiple sources and multiple sinks, cross layer design to meet the HRT requirements and RT support for the special application scenarios. From the above literature, it is observed that the issues like…”
Section: Challenges and Open Research Issues In Real Time Routing In Wsnmentioning
confidence: 99%
“…Likewise, WSNs have gained an immense attention for their ability in meeting the real time QoS guarantee in many time critical scenarios. In general, real time packet communication guarantee can be categorized as i) Hard Real Time (HRT) ii) Soft Real Time (SRT) [4][5][6][7][8]. HRT should support a deterministic dead time.…”
Section: Introductionmentioning
confidence: 99%
“…The generalization to 2-hop or more generally k-hop based routing has not been profoundly investigated despite interesting and possible [7]. An exploration will be helpful to provide a reference for future design and consideration, especially for the purpose in emerging real-time wireless sensor networks (WSN) [8] and some demanding applications [9].…”
mentioning
confidence: 99%
“…The MAC layer provides channel access to the next hop while the network layer provides the end-to-end transmission time. Using cross-layer design approach optimum results can be obtained [15].…”
Section: Introduction (Heading 1)mentioning
confidence: 99%
“…Wireless Sensor Networks has a wide range application namely, intruder tracking, medical care, health diagnosis and fire monitoring [15]. Industrial communication community ap-plications demands rigid end-to-end delivery and reliability [10] [13] under the constraints of wireless communication.…”
Section: Introduction (Heading 1)mentioning
confidence: 99%